Complete chloroplast genome of Vaccinium oldhamii and phylogenetic analysis. Issue 1 (2nd January 2019) - Kim, Sang-Chul; Baek, Seung-Hoon; Lee, Jei-Wan; Hyun, Hwa Ja
Abstract: The complete genome of Vaccinium oldhamii plastid was sequenced and analyzed in this study. The V. oldhamii plastid a circular genome of 173, 245 bp with 33 genes, including 88 protein, 37 tRNA, and eight rRNA genes. Phylogenetic analysis showed that species of Vaccinium were the first branching taxon In Ericaceae.